2020
DOI: 10.1002/jbm.a.36900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scaffold properties on adhesion and maintenance of boundary cap neural crest stem cells in vitro

Abstract: Optimal combination of stem cells and biocompatible support material is a promising strategy for successful tissue engineering. The required differentiation of stem cells is crucial for functionality of engineered tissues and can be regulated by chemical and physical cues. Here we examined how boundary cap neural crest stem cells (bNCSCs) are affected when cultured in the same medium, but on collagen‐ or laminin‐polyacrylamide (PAA) scaffolds of different stiffness (0.5, 1, or ~7 kPa). bNCSCs displayed marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Moreover, Nestin positive cells decreased over time for all cell lines except for hNSC#1: this is likely ascribable to an initially higher proliferation rate (until 1WIV) caused by an enriched percentage of stem/progenitor cells population that progressively faded into differentiating (or fate-committed) cells ( Figure 4G). To note, the obtained values can be easily modified with further customizations of HYDROSAP depending on the regenerative application: indeed we already demonstrated that by tuning different key experimental parameters (e.g., matrix stiffness, presence of functional motifs, and/or addition of neurotrophic factors) it is possible to modulate NSCs differentiation and improve differentiation toward neuronal fate (Jain et al, 2020): for example, we showed that increments of cell proliferation rate and neuronal differentiation is inversely proportional to the matrix stiffness, while stiffness and astrocytes number directly correlated (Cunha et al, 2011;Caprini et al, 2013;Han et al, 2020;Pandamooz et al, 2020). In future experiments, it will also be interesting to assess the influence of time-evolving viscoelastic properties of hydrogels over cellular behavior (Mattei et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, Nestin positive cells decreased over time for all cell lines except for hNSC#1: this is likely ascribable to an initially higher proliferation rate (until 1WIV) caused by an enriched percentage of stem/progenitor cells population that progressively faded into differentiating (or fate-committed) cells ( Figure 4G). To note, the obtained values can be easily modified with further customizations of HYDROSAP depending on the regenerative application: indeed we already demonstrated that by tuning different key experimental parameters (e.g., matrix stiffness, presence of functional motifs, and/or addition of neurotrophic factors) it is possible to modulate NSCs differentiation and improve differentiation toward neuronal fate (Jain et al, 2020): for example, we showed that increments of cell proliferation rate and neuronal differentiation is inversely proportional to the matrix stiffness, while stiffness and astrocytes number directly correlated (Cunha et al, 2011;Caprini et al, 2013;Han et al, 2020;Pandamooz et al, 2020). In future experiments, it will also be interesting to assess the influence of time-evolving viscoelastic properties of hydrogels over cellular behavior (Mattei et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…[ 350 , 351 , 352 ] Because the metal oxides are nonedible, scaffolds containing these coatings can be used only as temporary supports during the proliferation phase and will not be present in the final CM product. The stiffness, roughness, and wettability of the culture surface can also influence cell adhesion, [ 353 , 354 ] providing additional opportunities for CM producers to tune the adhesive properties of their scaffolding materials.…”
Section: Engineering Biological and Structural Complexitymentioning
confidence: 99%
“…Previous studies have underlined the effect of a scaffold's mechanical properties on the seeded cells. [ 15,16 ] Many cells are mechanosensitive, making them responsive to the mechanical cues from the environment. Surface morphology and stiffness are parameters that could modulate cell behavior.…”
Section: Requirements and Challengesmentioning
confidence: 99%